2023
DOI: 10.1177/00033197231161903
|View full text |Cite
|
Sign up to set email alerts
|

Naples Prognostic Score and Prediction of Left Ventricular Ejection Fraction in STEMI Patients

Abstract: The Naples score is a new prognostic score developed according to inflammatory and nutritional status and frequently evaluated in cancer patients. The present study aimed to evaluate using the Naples prognostic score (NPS) to predict the development of decreased left ventricular ejection fraction (LVEF) after acute ST-segment elevation myocardial infarction (STEMI). The study has a multicenter and retrospective design and included 2280 patients with STEMI who underwent primary percutaneous coronary interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…NPS, first associated with poor prognosis in cancer patients, provides valuable information regarding prognosis in STEMI patients in more recent studies. 28, 29 Birdal et al 30 showed a relationship between NPS and low ejection fraction in patients with STEMI. Karakoyun et al 31 showed the relationship between NPS and acute kidney injury in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…NPS, first associated with poor prognosis in cancer patients, provides valuable information regarding prognosis in STEMI patients in more recent studies. 28, 29 Birdal et al 30 showed a relationship between NPS and low ejection fraction in patients with STEMI. Karakoyun et al 31 showed the relationship between NPS and acute kidney injury in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several data for the prognostic significance of the NPS in cardiovascular diseases such as acute coronary syndrome and heart failure has recently been introduced to the literature 10,18,20 . Beyond the prognostic significance of the NPS, Birdal et al 25 have recently described a relationship between the NPS and the low left ventricular ejection fraction in patients with ST‐elevation myocardial infarction. Moreover, Ozkan et al 19 have compared the NPS with several inflammatory markers in predicting coronary artery severity.…”
Section: Discussionmentioning
confidence: 99%
“…8 diseases such as acute coronary syndrome and heart failure has recently been introduced to the literature. 10,18,20 Beyond the prognostic significance of the NPS, Birdal et al 25 have recently described a relationship between the NPS and the low left ventricular ejection fraction in patients with ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 ] Lately, several studies have been published on STEMI and NPS. Birdal et al [ 10 ] showed that NPS was reversely associated with discharge LVEF in STEMI patients. Saylik et al [ 13 ] demonstrated that NPS was independently associated with long-term mortality in patients with STEMI undergoing primary percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%